More pieces for the puzzle: novel information on the genetic diversity and population structure of Steno bredanensis (Artiodactyla: Delphinidae) in Central America and the Caribbean Sea - Barragán-Barrera, Dalia C. (2023)
Introduction: The rough-toothed dolphin (Steno bredanensis) inhabits oceanic waters of tropical latitudes and exhibits philopatry in some oceanic islands. However, the species has been observed in shallow coastal waters in a few areas. Particularly in Central America, the rough-toothed dolphin has been reported by occasional records and strandings. For instance, the first confirmed record of this species in the Panama’s Caribbean was on July 17, 2012, in a coastal region of the Chiriquí Lagoon during a bottlenose dolphin monitoring survey. Similarly, the first rough-toothed dolphin mass stranding reported for the Pacific of Panama was on April 20, 2016, at the Ostional Beach, where 60 dolphins stranded and ten died. These sightings and events offered a valuable opportunity to obtain samples to conduct genetic studies, which are scarce in the region. Objective: In this study, we present the first assessment of genetic diversity for rough-toothed dolphins based on mitochondrial DNA Control Region (mtDNA-CR) in the Panamanian Pacific and the Wider Caribbean. Methods: Samples were collected in Colombia (N=5), Panama (N-Caribbean=1, N-Pacific=9), and Puerto Rico (N=3) from free-ranging and stranded individuals. DNA was extracted from each sample, and a mtDNA segment of around 534 to 748 bp was amplified through the PCR reaction. The obtained sequences were compared with rough-toothed dolphin haplotypes previously published in NCBI (N=70), from the Atlantic, Indian, and the Pacific Oceans. Results: Our findings showed significant population structure among ocean basins (strong differentiation with ΦST data), and high genetic diversity within each phylogroup. Only the Atlantic Ocean showed high genetic differentiation within the basin, detecting three phylogroups: the Caribbean, northern, and southern Atlantic. Conclusions: These findings support previous genetic studies that indicate high levels of population structure among ocean basins, although this species seems to be widely dispersed. However, samples from Panama and the Caribbean appear to show connectivity between highly differentiated Atlantic and Pacific Oceans. Therefore, our results highlight the need for more research to assess the rough-toothed dolphin genetic and population status in Central America, as the piece of the puzzle needed to clarify its taxonomy and genetic differentiation worldwide. This information is needed due to the rough-toothed dolphin IUCN categorization as “Least Concern” and its classification into appendix II according to CITES. While individuals are potentially threatened by incidental fishing, no management units are currently used to conserve this species despite its high genetic differentiation.